2014
DOI: 10.2527/jas.2013-6783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of 2-hydroxy-4-methylselenobutanoic acid on growth performance and tissue selenium retention in growing pigs1

Abstract: The aim of this study was to compare the efficacy of a new organic Se (2-hydroxy-4-methylselenobutanoic acid [HMSeBA]) source (SO) with sodium selenite (SS) and selenized yeast (SY) at various dietary levels for growth performance and tissue Se deposition in growing pigs. A total of 112 crossbred (Pietrain × [Large White × Landrace]) gilts were allotted at an average body weight of 26.73 kg to 7 dietary treatments with 8 replicate pens of 2 pigs per pen. Pigs were fed basal diets unsupplemented or supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 43 publications
4
33
0
2
Order By: Relevance
“…Previous ruminant reports have similarly demonstrated that Se organic sources outperformed SS in terms of bioavailability at different ages and physiological status (Weiss, 2003;Ceballos et al, 2009). In this regard, HMSeBA supplementation increases eggs and muscle Se enrichment in poultry (Briens et al, 2013;Jlali et al, 2013) and pigs (Jlali et al, 2014). Organic Se supplementation ameliorated the HSinduced imbalances in the oxidant and antioxidant systems.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previous ruminant reports have similarly demonstrated that Se organic sources outperformed SS in terms of bioavailability at different ages and physiological status (Weiss, 2003;Ceballos et al, 2009). In this regard, HMSeBA supplementation increases eggs and muscle Se enrichment in poultry (Briens et al, 2013;Jlali et al, 2013) and pigs (Jlali et al, 2014). Organic Se supplementation ameliorated the HSinduced imbalances in the oxidant and antioxidant systems.…”
Section: Discussionmentioning
confidence: 77%
“…However, when feedstuffs are Se deficient or Se requirements are transiently increased, supplemental Se (even at the maximum regulatory allowance) might be insufficient. Utilizing organic minerals is a feasible strategy to improve their bioavailability, as feeding HMSeBA improved Se concentration in blood and milk in lactating dairy cows (Sun et al, 2017) and has been shown to enrich other tissues in different species (Briens et al, 2013;Jlali et al, 2013;Jlali et al, 2014). Thus, we hypothesized the beneficial effects of HMSeBA could be further enhanced during an oxidative stress inducing condition, such as HS (Aréchiga et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other minor organic forms derived from plants or yeast metabolisms such as methylselenol, selenohomocysteine, and selenoadiosine have been reported due to the progress in analytical methodology of analysing Se-species (Bierla et al, 2012). More recently, a feed additive as, hydroxy-selenomethionine, (2-hydroxy-4-metylselenobutanoic acid or HMSeBA) was indicated to be more bioavailable than selenite and Se-yeast in monogastrics (Briens et al, 2013;Jlali et al, 2014;Zhao et al, 2017Zhao et al, , 2014.…”
Section: Sources Of Seleniummentioning
confidence: 99%
“…A more recent study showed that greater Se accumulation in both natal and foetal tissues was associated with organic Se . In addition, the organic Se source hydroxy-selenomethionine, (2-hydroxy-4methylselenobutanoic acid or HMSeBA) when supplementated to growing pigs showed a higher deposition of Se in muscle compared to selenized yeast (Jlali et al, 2014). Likewise, in laying hens, the provision of HMSeBA increased Se deposition in eggs and breast muscle compared with other Se sources (sodium selenite and selenized yeast) (Jlali et al, 2013).…”
Section: Pig Diseasesmentioning
confidence: 99%